Changes of serum human epididymis protein 4 concentrations in chronic kidney disease and the relationship between serum HE4 and renal fibrosis - YANG Ping-zhen; HAN Hong-ling (Linchuang shenzangbing zazhi)
Objective To analyze the change of serum human epididymis protein 4 concentrations in chronic kidney disease and the relationship between serum HE4 and renal fibrosis.Methods In190 female patients at different stages of chronic kidney disease(CKD) with no ovarian and lung cancer,HE4 concentrations were analyzed by using Enzmy-linked immunosorbent assay(ELISA).Renal function was evaluated by measuring serum creatinine and urea concentrations.Estimated glomerular filtrationn rate(eGFR) was calculated by the MDRD formula,eighty-nine cases of CKD with stage 1 to 3 were divided into glomerulosclerosis group and no glomerulosclerosis group according to the renal pathological changes.Analyze the relationship between serum HE4 and renal fibrosis.Results The levels of serum HE4 in CKD group are differences(P<0.01).The levels of serum HE4 were significantly higher in the chronic renal insufficiency group(CKD2、CKD3、CKD4、CKD5groups) than those in normal renal function(P<0.05).The levels of serum HE4 were higher in CKD1 group than those in CKD2 group(P<0.05),The levels of serum HE4 were higher in CKD2 group than those in CKD3 group(P<0.001),The levels of serum HE4 were higher in CKD3 group than those in CKD4 group(P<0.001),The levels of serum HE4 were higher in CKD4 group than those in CKD5 group(P<0.001).The relationship between serum HE4 and GFR showed a negative nonlinear correlation.Results Serum HE4 concentrations showed no difference among glomerulosclerosis group and no glomerulosclerosis group(P>0.05).Conclusions HE4 concentrations may be elevated in CKD patients with no ovarian and lung cancer.Thus,HE4 results should be interpreted cautiously in women with renal disorders.Whether serum HE4 concentrations can become the indicator of renal fibrosis in patients with chronic kidney remains to be clinical research.